Sala de aula como recurso no processo de ensino e aprendizagem da disciplina de biologia - Ucelli, Leonardo (2019)
With the increasing use of technological resources by young people, a virtual classroom can be an incentive for learners to have a greater interest in taught content. We used to do this work the Google application, Google Classroom, to create virtual classrooms. Initially, students were offered some content previously addressed in the classroom for further study. Subsequently, the contents were made available before being approached in the classroom, which allowed students the possibility of building autonomy in their learning and experimenting with the inverted room methodology. The topics used for these activities were human reproduction, Mendelian genetics, blood group genetics, and the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR), the acronym used to represent the process of editing DNA. Different types of media were used in virtual classrooms, such as texts, images, animations, concept maps and video lessons, all available for free on websites such as Youtube, Biology blogs and Education Portals. In the second stage of the activity, students had the opportunity to create their own material for posting. Several videos, where they covered topics related to sexuality, were made available in the classroom or published on Youtube. Another activity with student protagonism was the creation of concept maps, which were made entirely by the students and posted in the application for sharing. For the analysis of the activity, a pre-test was applied, in the form of a questionnaire that sought initial information about the participating public, and at the end of the work, a post-test, to make quantitative and qualitative surveys about the students' perceptions of the media and the methodology used that most pleased the students. Based on the results presented, it was possible to observe that in the students' perception, the media and the methodology that most favored their learning were the video lessons and the content available before the class. This work provided students with knowledge of different learning methodologies, in which content was available before and after class, with an Flipped Classroom experience, and the results showed that they are interested in activities that promote their learning autonomy in the teaching and learning process.